UTILIZING AUDACITY AUDIO-RECORDING SOFTWARE TO IMPROVE CONSECUTIVE AND SIMULTANEOUS INTERPRETING SKILLS - Sumarni, Laurentia (Sanata Dharma University Yogyakarta, 2017)
In interpreting, the biggest problem is the evaluation of students’ performance in consecutive interpreting and simultaneous interpreting. The large number of students in the class leads to the small amount of time distributed to evaluate students’ interpreting effectively. To overcome this problem, the Audacity audio-recording software is used to help students practice interpreting independently and to help the lecturer to conduct interpreting tests simultaneously. The classroom action research aims to find out how the teaching learning process is conducted and how the students use Audacity to improve their consecutive and simultaneous interpreting skills. This research was conducted to 25 seventh-semester students taking the Interpreting class. The research instruments were Reflection Sheet and Lecturer’s Field Notes. From the students’ reflection and Lecturer’s Notes, most students understood the phases of interpreting and some students were still confused to differentiate between consecutive and simultaneous interpreting. The skills that they developed during the course were concentrating, listening, taking notes, paraphrasing, and public speaking. The use of Audacity was able to help them practice consecutive and simultaneous interpreting skills. An in-depth research to find out students’ perception on the use of Audacity to improve their consecutive and simultaneous interpreting skills must be conducted.DOI: https://doi.org/10.24071/ijiet.2017.010208